2017
DOI: 10.1111/1440-1681.12770
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of serotonin‐induced effects in peripheral artery disease observed through the femoral artery response in models of diabetes and vascular occlusion: The role of calcium ions

Abstract: Recent findings have demonstrated that serotonin is an important participant in the development and progression of peripheral artery diseases. Taking this into consideration, the goals of this study were to investigate the effects of serotonin on isolated Wistar rat femoral arteries in both healthy and diabetic animals, with and without artery occlusion, with a particular focus on determining the role of calcium in this process. Contraction experiments with serotonin on intact and denuded femoral artery rings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The femoral artery (FA) is a large conduit vessel from the lower limb circulation, formed in humans after completion of the iliofemoral system. Like in other mammalian conduit vessels, it responds to various contractile stimuli, i.e., α 1 ‐adrenoreceptor agonists, 5‐hydroxythryptamin, endothelin‐1, eicosanoids, NO inhibition, etc 4–8 . It is common knowledge that basal and agonist‐induced contractility of the FA could be altered by pathological conditions such as hypoxia, gram‐negative bacterial endotoxins, diabetes or microgravity 5,9–11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The femoral artery (FA) is a large conduit vessel from the lower limb circulation, formed in humans after completion of the iliofemoral system. Like in other mammalian conduit vessels, it responds to various contractile stimuli, i.e., α 1 ‐adrenoreceptor agonists, 5‐hydroxythryptamin, endothelin‐1, eicosanoids, NO inhibition, etc 4–8 . It is common knowledge that basal and agonist‐induced contractility of the FA could be altered by pathological conditions such as hypoxia, gram‐negative bacterial endotoxins, diabetes or microgravity 5,9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Like in other mammalian conduit vessels, it responds to various contractile stimuli, i.e., α 1 -adrenoreceptor agonists, 5-hydroxythryptamin, endothelin-1, eicosanoids, NO inhibition, etc. [4][5][6][7][8] It is common knowledge that basal and agonist-induced contractility of the FA could be altered by pathological conditions such as hypoxia, gram-negative bacterial endotoxins, diabetes or microgravity. 5,[9][10][11] Augmented vascular tone often coincides with advanced age, as at present, it is well appreciated that ageing increases muscle sympathetic nerve activity.…”
Section: Introductionmentioning
confidence: 99%
“…In the first part of this study, adenosine produced the concentration-dependent relaxation of the rat FA in all of the groups/subgroups. This response of FA was not surprising, since it is well known that adenosine mainly produces vasorelaxant effects [1,19,20]. The adenosine-induced relaxation was endothelium-dependent in all of the groups/subgroups, except in a group of animals with alloxaninduced diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…The monoamine neurotransmitter serotonin (5-HT) regulates a number of physiological and pathophysiological processes (Watts et al, 2012;De Ponti, 2004;Švob Štrac et al, 2016;Hornung, 2003), and is known to play an important role in the development and progression of peripheral artery disease (PAD) (Stojanović et al, 2017). In fact, a recent study found that 5-HT serum levels were markedly elevated in PAD patients (Senol and Es, 2015), implying it may play a role in the development and/or progression of this disease.…”
Section: Introductionmentioning
confidence: 99%